Об одном методе построения отношений между персональными данными в социальных сетях - Абдуллаева, Ф.Д. (Проблемы управления и информатики, 2009)
Проведено аналіз властивостей і можливостей соціальних мереж. Розглянуто перелік можливих відношень між персональними даними в середовищі розподіленої інформаційної системи «Населенння і міграція». Наведено приклад обчислення відношення сусідства між персональними даними. The analysis of properties and potential of social networks is performed. Different variants of definition of concept of social networks are given. The possible relations between the personal data in the environment of the distributed information system «Population and migration» is listed. The example of calculation of the neighbourhood relation between the personal data is presented